PEMANFAATAN DESAIN GRAFIS SEBAGAI MEDIA PROMOSI UNTUK MENUNJANG PENJUALAN BUKU KOMIK ULTIMATE GLAD - Ayyub H.B.N.MS; Arsito Ari Kuncoro; Fendy Suhono; Mufadhol Mufadhol (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2022)
Technological developments are also needed in the field of communication, especially in the book publishing industry. Now, the comic industry in Indonesia is very busy, where almost all bookstores in big cities sell various types of comics. However, what is quite worrying is that most of the comics sold in these bookstores are translated comics. The dream about the rebirth of Indonesian comics as a renaissance is far from reality, although it is possible that it will rise again in the future. Moreover, with the entry of imported comics from Europe, East Asia, and America, the position of local comics is increasingly pressing. Moreover, Indonesian comics are also losing interest, because they are dominated by Japanese and Korean comics. Through these problems, efforts to promote Ultimate Glad comics need to be done creatively, namely promoting comics using the Merchandise method. Creative here is not just using promotional media, but how to promote efforts to get awareness and engagement of old consumers or new potential customers through direct interaction between merchandise products and consumers. Merchandise as the most appropriate promotional media because it can win the competition in attracting the attention of consumers. With a very unique and attractive design, it will be easier to introduce the "Ultimate Glad" comic to potential consumers, especially teenagers and comic lovers in Indonesia.